Evaluation of Creatinine Levels as an Indicator of Kidney Function in Diabetes Mellitus Patients at RSU Haji Medan - Herlina Herlina (Institut Kesehatan Medistra Lubuk Pakam, 2025)
Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disorder that can lead to serious complications, including impaired kidney function. Serum creatinine is one of the key parameters used to evaluate renal function in diabetic patients, as its concentration remains relatively stable and is not significantly influenced by protein intake. This study aimed to assess the profile of serum creatinine levels in patients with T2DM at RSU Haji Medan as an early indicator of potential renal complications. A descriptive study with a cross-sectional design was conducted. The study involved a total of 25 hospitalized T2DM patients who underwent serum creatinine testing. All available medical records were included as the sample. Out of 25 patients, 15 (60%) showed creatinine levels within the normal range, while 10 patients (40%) had elevated creatinine levels. The mean creatinine concentration was 2.42 mg/dL in male patients and 0.85 mg/dL in female patients. The findings indicate that a portion of T2DM patients have already experienced reduced kidney function. Regular monitoring of serum creatinine is essential for early detection and prevention of diabetic kidney complications.